Creating learning solutions for executive education programs. Issue 1 (March 2018) - Dover, Philip A.; Manwani, Sharm; Munn, David
Abstract: Executive education is both a growing and increasingly competitive industry. The traditional business school, once a dominant player in this space, now faces competition from sophisticated and focused consultants and for-profit training specialists offering a variety of face-to-face and on-line instructional vehicles. An abiding question has become ever more prevalent for business schools – are executive education clients getting meaningful, long-term value for their significant investments? Demonstrating value and building capabilities is different for a generic, open enrolment course than for a custom program. This paper proposes a solutions-based approach to the development and implementation of customized executive programs, arguing that the tailored customer focus and the operational rigor of a solutions perspective leads to sustainable and measurable client value both at the individual and corporate level. A case study involving a global high technology company is used to demonstrate the steps required to apply a solutions roadmap. The results show that a solutions approach – carefully and collaboratively undertaken in selected settings – can provide considerable benefits to both client and provider. Further research is proposed to validate and develop the learning points. Highlights: The article describes a solutions-based approach to the design and delivery of executive education programs. The increasingly competitive environment facing traditional business schools is emphasized. A Customer Solutions Framework represents the executive education market on both the level of customer specificity and the nature of customer needs. This is complemented by a Solutions Capabilities Roadmap which allows business schools to move through a number of stages to solutions mastery. The viability of our "solutions based" framework was critically assessed through the detailed analysis of a recent executive program. The findings reveal that a solutions approach to executive education can have considerable benefits to business schools and their clients.